7C.001 Changing drug overdose deaths patterns where US rates are highest: global implications. (14th March 2021) - Smith, Gordon; Dai, Zheng; Abate, Marie; Mock, Allen; Kramer, James
Abstract : Background: Rural West Virginia leads the US in overdose deaths. The role of multiple drug combinations in fatality trends is unclear especially given rapid increases in methamphetamine involvement. Methods: Toxicology data from our WV Forensic Drug Database contains drug levels on all drug-involved deaths in WV, including determinations if drugs caused or contributed to death. Trends from 2013 to 2018 were examined including separate methamphetamine analyses. Results: Death rates increased dramatically to 49.6/100, 000 with most deaths involving poly-substances with fentanyl. Heroin-related deaths increased from 138 to 257 in 2017, falling in 2018, as did prescription drug deaths. Methamphetamine involvement increased 12-fold (28 cases in 2013 to 336 cases in 2018). Most methamphetamine-related deaths (N=815) involved other drugs (only 25% involved methamphetamine alone). Opioids were present in 63.8% of methamphetamine deaths; fentanyl/FAs having the largest increase (4% 2013, to 49% in 2018) and prescription opioids decreased by over 100%. Despite increasing methamphetamine deaths, proportions with only methamphetamine did not change over time. Heroin presence without fentanyl/FAs steadily decreased for methamphetamine-involved deaths; by 2018, only 2% had heroin present without fentanyl/FAs. Discussion: Drug-related deaths in this rural state continue to increase and most involve multiple drugs with a rapid rise in methamphetamine over the past three years. Unlike urban drug problems, the origins of the WV epidemic are largely iatrogenic, starting with extremely high opioid prescription rates. This presentation will outline the progression of the rural drug problem in WV, describe harm-reduction efforts and include more detailed statistical modeling of trends.